Claridge's : the cookbook - Nail, Martyn; Erickson, Meredith, 1980- (Mitchell Beazley, 2017)
An art deco jewel set in the heart of London's Mayfair, Claridge's - one of the world's best luxury hotels - has long been known for inspiring menus and exceptional dining from breakfasts and brunches, through lunch and afternoon tea, and on to drinks, dinner and the dessert cart. Claridge's: The Cookbook celebrates that heritage in style, with a collection of over 100 of the best-loved dishes and drinks from The Foyer, The Reading Room, the Bar and The Fumoir. With interludes ranging from the return of the "drunch" to the magic of Christmas, the extraordinary experience of dining at Claridge's is brought to life in book form.